젊은 남성에서 팔씨름에 의해 발생한 상완골 간부 골절 - 이승림; Seung Rim Yi; 권지은; Jieun Kwon; 이예현; Ye Hyun Lee; 양보규; Bo Kyu Yang; 안영준; Young Joon Ahn; 임세혁; Se Hyuk Im; et al. (대한스포츠의학회지, 2017)
Humeral shaft fracture sustaining arm wrestling is rare, but occurs intermittently. We treated 15 cases of humeral shaft spiral fractures occurred during arm wrestling for fun since 2007. Average age was 22.47±2.69 years, average body mass index was 22.67±2.06 kg/m 2 . There was no prominent tendency for the fractures to occur at a certain phase of the match. Fractured level and length of each case were measured in the plain radiographs and compared with those of previous reports. Eight cases (53.3%) had an associating medial butterfly fragment, and the time taken until the fracture occurred was longer than that of simple spiral fracture (15.62±9.03 seconds vs. 7.85±2.67 seconds, p=0.048). Fractures were distributed mid to distal one third of humerus, the length of fracture was 7.93±2.69 cm and involved 25.43%±8.24% of humeral length. All cases except one treated surgically using plate and screws and returned their full activities within postoperative 3 months. Although arm wrestling is a simple and joyful sport, participants should be aware of the risks of injury during arm wrestling, especially for the amateur players.